Investigations on the Effects of Dietary Essential Oils and Different Husbandry Conditions on the Gut Ecology in Piglets after Weaning. (7th May 2009) - Janczyk, P.; Pieper, R.; Urubschurov, V.; Wendler, K. R.; Souffrant, W. B.
Abstract : Essential oils (EO) are being considered as possible alternatives to in-feed antibiotic growth promoters in pig nutrition. The effects of an EO mixture consisting of limonene, eugenol and pinene (10.0, 2.0, and 4.8 mg/kg diet, resp.) on gut physiology and ecology were studied in piglets. The experiment was conducted at low (commercial farm) and high hygienic conditions (experimental farm), to elucidate interactions between EO supplementation and husbandry methods. Piglets were weaned at 28 days of age, when they were offered either a control diet (C) or C with EO. Four piglets were sacrificed in each group on day 29, 30, 33 and 39. Digesta from the third distal part of the small intestine and from the colon were sampled and analysed for pH, dry matter, lactic acid, short chain fatty acids and ammonia concentrations. Enterobacteria, enterococci, lactobacilli and yeast counts were obtained by plating. Genomic DNA was extracted from digesta and polymerase chain reaction—denaturing gradient gel electrophoresis was performed. Individual microbial communities were identified at each farm. Age affected the intestinal parameters. No effects of the EO with exception for a significant reduction in colon bacterial diversity at 39 days of age could be recorded at experimental farm.